Communication Strategy In Local Wisdom Development Towards Creative Economy of Coffee Village in Lampung - Yanti, Fitri; Putra, Andi Eka; Prastiwi, Herliana; Mansyur, M (Universitas Islam Negeri Raden Intan Lampung, 2024)
Local wisdom is an important asset in developing creative economy-based tourism villages. This research examines the communication strategy for developing local wisdom towards the creative economy in Kampung Kopi, Rigis Jaya Village, West Lampung, which combines the potential of coffee and local culture into a tourist destination. Qualitative research methods with a case study approach were used through interviews, observations, and document analysis. The results show that the communication strategy includes marketing, stakeholder communication, community participation, and education. The participatory approach is the key to success, as it involves the community in managing the tourism village. The communication strategy implementation has significantly enhanced tourist appeal, strengthened local cultural identity, and supported creative economy development through coffee-based products. This approach has transformed Rigis Jaya Village into a recognized destination while creating economic opportunities for residents. The conclusion states that local wisdom-based communication strategies can increase tourist attractiveness, strengthen cultural identity, and support the creative economy. This research serves as a reference for the development of other tourist villages in Indonesia.